The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1021/jacs.9b05583
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium(III)-Catalyzed Asymmetric Borylative Cyclization of Cyclohexadienone-Containing 1,6-Dienes: An Experimental and DFT Study

Abstract: Because of the inherent difficulty in differentiating two olefins, the development of metal-catalyzed asymmetric cyclization of 1,6-dienes remains challenging. Herein, we describe the first rhodium(III)-catalyzed asymmetric borylative cyclization of cyclohexadienone-tethered mono-, 1,1di-, and (E)-1,2-disubstituted alkenes (1,6-dienes), affording optically pure cis-bicyclic skeletons bearing three or four contiguous stereocenters with high yields (25−93%), and excellent diastereoselectivities (>20:1 dr) and en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 54 publications
0
25
0
Order By: Relevance
“…Finally, other types of 1,3-enyne substrates were investigated. For longer tethered cyclohexadienone 4g, the in-situ generated chiral allenylcopper intermediate underwent direct protonation to form the optically pure 1,3-disubstituted allene 5g rather than conjugate addition to produce six-membered ring product, which demonstrated that the formation of sixmembered product was less favorable than five-membered one in this case, probably due to the ring strain 48 . In the previous report on Cu-catalyzed asymmetric semi-reduction of ketonetethered 1,3-enyne, only direct protonation product and no further cyclized product was detected 42 .…”
Section: Resultsmentioning
confidence: 86%
See 1 more Smart Citation
“…Finally, other types of 1,3-enyne substrates were investigated. For longer tethered cyclohexadienone 4g, the in-situ generated chiral allenylcopper intermediate underwent direct protonation to form the optically pure 1,3-disubstituted allene 5g rather than conjugate addition to produce six-membered ring product, which demonstrated that the formation of sixmembered product was less favorable than five-membered one in this case, probably due to the ring strain 48 . In the previous report on Cu-catalyzed asymmetric semi-reduction of ketonetethered 1,3-enyne, only direct protonation product and no further cyclized product was detected 42 .…”
Section: Resultsmentioning
confidence: 86%
“…Inspired by recent progress in the copper(I)-catalyzed asymmetric transformations of 1,3-enynes to functional chiral allenes and our continuous interest in catalytic asymmetric desymmetrization of cyclohexadienone derivatives [38][39][40][41][42][43][44][45][46][47][48] , we envisioned that the key axially chiral allenylcopper intermediate T1, generated from the chemo-, regio-, and enantio-selective insertion of 1,3enyne to chiral copper hydride species, would be rapidly trapped by the intramolecular enones to yield the desired chiral exocyclic allenes 2 with hopefully high enantioselectivity and diastereoselectivity ( Fig. 2d).…”
mentioning
confidence: 99%
“…A Rh(III)-catalyzed intramolecular carboboration has also been achieved by Tian, Hong, Lin and coworkers (Scheme 24). [50] Mechanistically, this reaction involves initial formation of a bisboryl-Rh(III) intermediate. Next, synmigratory insertion to the non-conjugated alkene leads to formation of an alkylrhodium intermediate that then undergoes conjugate addition to the tethered α,β-unsaturated alkene.…”
Section: Alkene Carboboration Catalyzed By Other Transition Metalsmentioning
confidence: 99%
“…Up until now, there are only two reports of success to our knowledge: one is Pdcatalyzed asymmetric silylative cyclization of 1,6dienes, which was developed by Widenhoefer and coworkers in 1999 with good enantioselectivities (Scheme 1a); [6] the other is Rh-catalyzed asymmetric borylative cyclization of cyclohexadienone-containing 1,6-dienes to afford bicyclic skeletons possessing three contiguous stereocenters in trans-cis form, which was just recently described by our group (Scheme 1b). [7] Herein, we present the first copper-catalyzed asymmetric borylative cyclization of 1,6-dienes (cyclohexadienone-tethered electron-rich terminal alkenes), affording bicyclic products bearing three consecutive stereocenters in cis-cis form with high yields and enantioselectivities, which is strongly appealing to complement Rh-catalyzed asymmetric methodology. [7] In 2008, Ito, Sawamura and coworkers reported the first Cu-catalyzed asymmetric borylative cyclization reaction that converted γ-silylated allylic carbonates into the optically active cyclopropane derivatives.…”
mentioning
confidence: 99%
“…[7] Herein, we present the first copper-catalyzed asymmetric borylative cyclization of 1,6-dienes (cyclohexadienone-tethered electron-rich terminal alkenes), affording bicyclic products bearing three consecutive stereocenters in cis-cis form with high yields and enantioselectivities, which is strongly appealing to complement Rh-catalyzed asymmetric methodology. [7] In 2008, Ito, Sawamura and coworkers reported the first Cu-catalyzed asymmetric borylative cyclization reaction that converted γ-silylated allylic carbonates into the optically active cyclopropane derivatives. [8] Subsequently, a handful of Cu-catalyzed asymmetric borylative cyclization reactions, initiated by the borylation of alkenes, were successively developed, separately using aryl-substituted allylic phosphates, [9] enone diketones, [10] and 2-styrylimines [11] as substrates.…”
mentioning
confidence: 99%